Enhancing CO2/CH4 separation performance and mechanical strength of mixed-matrix membrane via combined use of graphene oxide and ZIF-8 - Li, Wen (2020)
High-performance mixed-matrix membranes that comprise both zeolitic imidazolate framework-8 (ZIF-8) and graphene oxide (GO) were synthesized with a solution casting technique to realize excellent CO2/CH4 separation. The incorporation of ZIF-8 nanocrystals alone in ODPA-TMPDA polyimide can be used to significantly enhance CO2 permeability compared with that of pure ODPA-TMPDA. Meanwhile, the addition of a GO nanostack alone in ODPA-TMPDA contributes to improved CO2/CH4 selectivity. Hence, a composite membrane that contains both fillers displays significant enhancements in CO2 permeability (up to 60%) and CO2/CH4 selectivity (up to 28%) compared with those of pure polymeric membrane. Furthermore, in contrast to the ZIF-8 mixed-matrix membrane, which showed decreased mechanical stability, it was found that the incorporation of GO could improve the mechanical strength of mixed-matrix membranes. Overall, the synergistic effects of the use of both fillers together are successfully demonstrated in this paper. Such significant improvements in the mixed-matrix membrane's CO2/CH4 separation performance and mechanical strength suggest a feasible and effective approach for potential biogas upgrading and natural gas purification.